A flexible strain gauge exhibiting reversible piezoresistivity based on an anisotropic magnetorheological polymer - Mietta, José L. (2014)
A flexible, anisotropic and portable stress sensor (logarithmic reversible response between 40–350 kPa) was fabricated, in which i) the sensing material, ii) the electrical contacts and iii) the encapsulating material, were based on polydimethylsiloxane (PDMS) composites. The sensing material is a slide of an anisotropic magnetorheological elastomer (MRE), formed by dispersing silver-covered magnetite particles (Fe3O4@Ag) in PDMS and by curing in the presence of a uniform magnetic field. Thus, the MRE is a structure of electrically conducting pseudo-chains (needles) aligned in a specific direction, in which electrical conductivity increases when stress is exclusively applied in the direction of the needles. Electrical conductivity appears only between contact points that face each other at both sides of the MRE slide. An array of electrical contacts was implemented based on PDMS-silver paint metallic composites. The array was encapsulated with PDMS. Using Fe3O4 superparamagnetic nanoparticles also opens up possibilities for a magnetic field sensor, due to the magnetoresistance effects.